2014
DOI: 10.1186/1471-2431-14-64
|View full text |Cite
|
Sign up to set email alerts
|

Elevated arterial blood pressure and body mass index among Nigerian preschool children population

Abstract: BackgroundArterial blood pressure tends to rise with growth and development. Elevated blood pressure (EBP) in children usually occurs during the first two decades of life, and the children with hypertension tend to grow into adulthood with the high level of blood pressure. The prevalence of hypertension in children is increasing, the causes likely to be of different combination of factors. In this study we ascertained the prevalence of EBP in pre-school children in Enugu metropolis, South-East Nigeria and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
1
18
1
Order By: Relevance
“…Forty-four (44) independent studies [ 27 , 33 – 77 ] were included in this review. These studies were published between the years 1968 and 2015.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-four (44) independent studies [ 27 , 33 – 77 ] were included in this review. These studies were published between the years 1968 and 2015.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between the years 1968 and 2015. 41 studies [ 27 , 33 – 77 ] were conducted across the 6 geopolitical zones of Nigeria and 3 studies [ 37 , 73 , 75 ] were conducted nationally. The numbers of those conducted in the zones are as follows: south- west 15[ 35 48 , 54 59 , 64 , 67 , 68 ]; south-east 8 [ 27 , 42 , 47 , 51 – 53 , 63 , 66 , 74 ]; south-south 10[ 33 , 45 , 60 – 62 , 65 , 70 – 72 , 76 ]; north-central 4 [ 34 , 46 , 48 , 51 ]; north-east 1[ 49 ] and north-west 4 [ 39 , 40 , 50 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[613] However, in the Democratic Republic of Congo, a local study[37] documented that lower socioeconomic status was associated with elevated BP while Okoh and Alikor[11] in Port Harcourt, South-South Nigeria reported a high level of hypertension in school children with a family history of hypertension. A possible explanation for the lack of association between hypertension and family history of hypertension in this study may be the lack of awareness of most parents of their hypertensive status as observed in the recent systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The few local studies that evaluated risk factors for hypertension were limited to either the history of hypertension in the family and or the role of obesity/overweight. [1113]…”
Section: Introductionmentioning
confidence: 99%